Hippocampal neuroimmune response in mice undergoing serial daily torpor induced by calorie restriction - Cogut, Valeria; Goris, Maaike; Jansma, Aukje; van der Staaij, Marrit; Henning, Robert H. (Frontiers in Neuroanatomy, 2024)
Hibernating animals demonstrate a remarkable ability to withstand extreme physiological brain changes without triggering adverse neuroinflammatory responses. While hibernators may offer valuable insights into the neuroprotective mechanisms inherent to hibernation, studies using such species are constrained by the limited availability of molecular tools. Laboratory mice may serve as an alternative, entering states of hypometabolism and hypothermia similar to the torpor observed in hibernation when faced with energy shortage. Notably, prolonged calorie restriction (CR) induces serial daily torpor patterns in mice, comparable to species that utilize daily hibernation. Here, we examined the neuroinflammatory response in the hippocampus of male C57BL/6 mice undergoing serial daily torpor induced by a 30% CR for four weeks. During daily torpor episodes, CR mice exhibited transient increases in TNF-α mRNA expression, which normalized upon arousal. Concurrently, the CA1 region of the hippocampus showed persistent morphological changes in microglia, characterized by reduced cell branching, decreased cell complexity and altered shape. Importantly, these morphological changes were not accompanied by evident signs of astrogliosis or oxidative stress, typically associated with detrimental neuroinflammation. Collectively, the adaptive nature of the brain's inflammatory response to CR-induced torpor in mice parallels observations in hibernators, highlighting its value for studying the mechanisms of brain resilience during torpor. Such insights could pave the way for novel therapeutic interventions in stroke and neurodegenerative disorders in humans.